Implementation of an Integrated Longitudinal Curricular Activity for Graduating Pharmacy Students - Karimi, Reza (American Journal of Pharmaceutical Education, 2014)
Objectives. To evaluate whether a novel integrated longitudinal curricular activity to prepare graduating doctor of pharmacy (PharmD) students for 2 comprehensive examinations was successful, and to assess whether it engaged other pharmacy students in curricular discussion and learning. Design. Thirty-eight of 91graduating third-year (P3) students in a PharmD program formed 11 teams to create and present pharmacotherapeutic posters to their peers. The impact of the novel activity on graduating students’ performance on the North American Pharmacist Licensure Examination (NAPLEX) and a comprehensive commercial examination was assessed. All first-year (P1), second-year (P2), and P3 students reviewed and discussed the content of each poster. Assessment. Participants in the integrated longitudinal curricular activity performed better than nonparticipants on the commercial examination (p=0.023) and NAPLEX (p=0.033). However, regardless of participation, commercial examination scores predicted a significant amount of variance (ie, 34%) in NAPLEX scores. The P3 participants (83%) believed the curricular activity assisted them in their NAPLEX preparation, while 75% of P1 students, 79% of P2 students, and 80% of P3 students agreed that poster review provided an effective summary of different disease states. Ninety percent of faculty poster evaluators reported that the posters were professional, and all evaluators agreed that participants effectively conveyed their message to the intended audience. Conclusion. The integrated longitudinal curricular activity provided a positive learning environment for all pharmacy students and may have better prepared graduating students’ for the NAPLEX.